Patient-reported outcomes and experiences assessment in women with breast cancer: Portuguese case study - Coelho, Anabela (2023)
In 2020, female breast cancer was the most commonly diagnosed cancer worldwide, representing the type of cancer with the highest incidence among women and the second most common cause of cancer death among women in all OECD countries. The conventional measures addressing the burden of breast cancer by measuring mortality, incidence, and survival do not entirely reflect the quality of life and patients experience when receiving breast cancer care. The main objective of this study is to capture patient-reported outcomes and experiences in women with breast cancer in Portugal using methods developed for international benchmarking purposes, such as the OECD Patient-reported Indicators Surveys. The study included 378 women with breast cancer, with the age distribution being 19.8% aged 15 to 49 years and 80.2% aged 50 years and over. The data collection procedure and analysis followed the "OECD Breast Cancer Patient Reported Outcomes Working Group" protocol, allowing subsequent comparability with data from other OECD member countries. Most women were satisfied with the treatment outcome regarding the shape of their lumpectomy breast when wearing a bra (96.1%) and with the equal size of both breasts (78.3%). Findings on the WHO QOL-BREF showed that women manifest a lower score in well-being when compared with the general population or populations living with chronic diseases. This study shows the feasibility of implementing and using patient-reported metrics (PROM and PREM) in breast cancer services in Portugal. Measuring PROMs and PREMs from Portuguese women receiving breast cancer care provides insightful evidence into the quality and value of cancer care.